Distribution of Arsenic with Iron, Manganese and Copper in Borehole Sediments of the River Tista and Jamuna - Rahman, Mohammad Arifur; Alam, Md Jahangir; Siddique, Nur-E-Alam; Alam, AM Shafiqul (Dhaka University Journal of Science, 2013)
Boreholes sediments (1-6 m depth) of the river Tista and Jamuna in Bangladesh were collected for the analysis of As, Fe, Mn, Cu and organic carbon. Chemical analysis reveals that Mn and Fe hydroxides and organic matter are the major leachable solids which carrying As. High levels of arsenic concentration in aquifers are associated with fine grained sediments at the lower depth of the sediment layer. The highest As containing sediment was gray and texture of sediment was clay type. The colour of the least As containing sediment was white and texture of sediment was sandy. In addition, this study indicate that As is closely associated with Fe and slightly correlated with Mn and Cu in the sediment of the river Tista and Jamuna. Arsenic was distributed regularly DOI: http://dx.doi.org/10.3329/dujs.v61i2.17072 Dhaka Univ. J. Sci. 61(2): 207-210, 2013 (July)